Acute Sarcomeric M-Line Disease Associated With ATP Synthase Subunit α Autoantibodies in Ankylosing Spondylitis. Issue 11 (12th September 2018) - Guglielmi, Valeria; Vattemi, Gaetano; Cecconi, Daniela; Fracasso, Giulio; Marini, Matteo; Tomelleri, Giuliano
Abstract: M-line is the narrow transverse band located in the center of the sarcomeric A-band that is mainly responsible for the stabilization of myosin thick filaments. A 27-year-old male patient with a positive medical history for ankylosing spondylitis presented with one month of proximal upper limb muscle weakness associated with pain on both acromioclavicular joints. A biopsy of deltoid muscle documented the disappearance of M-line, the misalignment of myofilaments, and the loss of the distinction between the A and I bands. Complete resolution of muscle weakness occurred after one year of treatment with antiTNFα agent Etanercept. Because of the acute onset of symptoms and the recovery after immunosuppressive treatment we hypothesized that an immune-mediated mechanism was responsible for the muscle disorder. The serum IgG-mediated autoreactivity to skeletal muscle antigens resolved by bidimensional electrophoresis was assessed in the described patient and compared with that of control subjects. The comparative analysis of the immunoreactive spots revealed that ATP synthase subunit α is specifically recognized by patient's serum, suggesting that the protein might represent a putative antigenic target in the disease. This study reports an acute reversible myopathy pathologically characterized by M-line involvement and associated with serological antibodies to the subunit α of ATP synthase.